Mechanical and Thermal Properties of Chemically Modified Epoxy Resin - Ikram, Sumeera; Munir, Arshad (Scientific Research, 2012)
Diglycidyl ether of bisphenol-A (DGEBA), having number average molecular weight (Mn) 375, was modified by incorporating the hydroxyl terminated polybutadiene (HTPB) based prepolymer using isophorone diisocyanate as a coupling agent. To increase the compatibility between the epoxy resin and HTPB part, polar groups were introduced in the later to achieve physical and chemical interactions between the two phases. The finally modified DGEBA system was cured with amine based hardener. FTIR and 1 H-NMR were used to monitor the whole modification procedure. The rubber particles size and distribution was monitored as a function of HTPB contents in the resin system using scanning electron microscopy (SEM). The mechanical, thermal and thermo-mechanical properties have shown that the tensile strength, toughness, ductility and impact strength of the modified cured system have been successfully increased at some optimum HTPB contents without affecting the inherent thermal and thermo-mechanical stability associated with DGEBA resin system. Some of the mechanical properties like flexural modulus, tensile modulus and compressive strength decreased with increasing rubber contents.
Keywords: DGEBA; HTPB; Impact Strength; Thermo-Mechanical; Mechanics Properties